A New Unequal Clustering Method for Energy Efficient Computation in WSN Using Cuckoo Search Based Particle Swarm Optimization (CBPSO) - Sharma, K; Chaudhary, N (International Journal of Computer Sciences and Engineering, 2025)
There have been recent advances in micro-electro-mechanical systems (MEMS) technology, wireless communications, and digital electronics. These advances have enabled the development to low-cost, low-power, multifunctional sensor nodes that are small in size and communicate with each other using radio frequencies. They have limited processing capabilities, transmission range, and most importantly available energy. For load balancing and efficient data collection in the network, clustering is used. Sensors in each cluster send the data to their corresponding cluster heads. The cluster head performs data aggregation and transmission of the aggregated data to the base station. This paper proposes a methodology to achieve load balancing & cluster head selection using cuckoo search algorithm and cluster formation is done using particle swarm optimization algorithm in anticipation of minimizing energy consumption and network lifetime